HEMATOLOGYCAL CONDITION OF TILAPIA (Oreochromis niloticus) THAT WERE INFECTED BY ECTOPARASITES IN PONDS IN SIMPANG TIGA SUB-DISTRICT PEKANBARU - Isnaini Lidya Rizki; Morina Riauwaty; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was conducted in July to September 2014 in Parasite and Fish Diseases Laboratory of Fisheries and Marine Science Faculty, Riau University. The aim of this research to understand the hematologycal condition of tilapia (Oreochromis niloticus) that were infected by ectoparasites. The method used in this study is a survey method by taking fish samples from one location and the fish sample will be taken in the laboratory and identified. Ectoparasite examinations will be done based on Kabata, 1985 and hematologycal parameter will be measured based on Siwicki and Anderson, 1993. Result shown that the three types of ectoparasites that were infected in tilapia are: Trichodina sp., Dactylogyrus sp., and Gyrodactylus sp. The average of hematocrit value of male tilapia was 19,7- 22,18%, the hemoglobin concentration was 4.07-4.8%, and the total erythrocyte was 1.483.000-1.680.000 cells / mm3, whereas the hematocrit of female tilapia was 18,9-21,6%, the hemoglobin concentration was 3,8-4,9%, the total erythrocytes was 1.346.000-1.562.500 cells / mm3. It can be concluded that the hematologycal conditions of tilapia (male and female) in that area was different.Keywords : Ectoparasites, Hematologycal, Tilapia, Pekanbaru